2004
DOI: 10.1093/humrep/deh007
|View full text |Cite
|
Sign up to set email alerts
|

An association between sex chromosomal aneuploidy in sperm and an abortus with 45,X of paternal origin: possible transmission of chromosomal abnormalities through ICSI

Abstract: This study indicates that the paternal origin of the 45,X abortus was likely the result of a high level of nullisomy in the sperm and provides evidence for the transmission of chromosomal abnormality from sperm to the conceptus through ICSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 28 publications
2
22
0
5
Order By: Relevance
“…The methods of sperm preparation, probe hybridization, and FISH analysis were described previously [6]. Probe specificity and the labeling efficiency of each probe were confirmed on karyotyped blood leukocytes prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of sperm preparation, probe hybridization, and FISH analysis were described previously [6]. Probe specificity and the labeling efficiency of each probe were confirmed on karyotyped blood leukocytes prior to analysis.…”
Section: Methodsmentioning
confidence: 99%
“…ICE were analyzed as previously reported [7]. Sperm were scored as previously described [6]. Chi-square test was used to compare the aneuploidy rates in the patient with controls.…”
Section: Methodsmentioning
confidence: 99%
“…Another group studied the incidence of sex chromosomal aneuploidies in a male with a previous miscarriage with Turner syndrome of paternal origin. This study reported a significant increase in sex chromosomal disomies and nullisomies compared to the control group (Tang et al, 2004).…”
Section: Sex Chromosomesmentioning
confidence: 45%
“…В останній час значна увага в області репродуктивної медицини приділяється вивченню помилок геному батька. Допоміжні репродуктивні технології (ДРТ), такі, як стандартне екстракорпо-рального запліднення, і, особливо, інтрацитоплаз-матична ін'єкція сперматозоїдів (ІКСІ), дозволяють парам зі значними порушенням показників класич-ної спермограми отримати вагітність, тоді як кілька років тому ці пари були б змушені використовувати донорство сперми для того, щоб отримати дитину [1][2][3][4].Тим не менш, можна обговорювати здатність зразків сперми низької якості до генерації ембріо-нів з нормальним потенціалом розвитку.…”
Section: Zhilkova@feskovcomuaunclassified
“…В останній час значна увага в області репродуктивної медицини приділяється вивченню помилок геному батька. Допоміжні репродуктивні технології (ДРТ), такі, як стандартне екстракорпо-рального запліднення, і, особливо, інтрацитоплаз-матична ін'єкція сперматозоїдів (ІКСІ), дозволяють парам зі значними порушенням показників класич-ної спермограми отримати вагітність, тоді як кілька років тому ці пари були б змушені використовувати донорство сперми для того, щоб отримати дитину [1][2][3][4].Тим не менш, можна обговорювати здатність зразків сперми низької якості до генерації ембріо-нів з нормальним потенціалом розвитку.Однією з причин порушень у розвитку ембріо-нів на преімплантаційному етапі або вагітності, що вже наступила, є генетичні аномалії у сперматозої-дах -підвищений рівень фрагментації ДНК та хро-мосомні зміни [3][4][5][6][7]. Важливим критерієм нормаль-ного розвитку ембріону є формування бластоцисти високої морфологічної якості на п'ятий день розви-тку [8,9].…”
unclassified